Spectrophotometric Determination of Mesalazine Via Arsenazo III- Cerium(III) Reaction - Zeena Z. Al-Abdaly (College of Education for Pure Sciences, 2011)
Abstract A simple and sensitive spectrophotometric method has been developed for the determination of mesalazine (5-aminosalicylic acid) in pure form and in its pharmaceutical preparation(capsule). The method is based on the oxidation-reduction reaction between mesalazine and cerium (IV) ion, then reaction of cerium(III) with arsenazo III reagent in acidic medium to produce a green-blue complex, which is stable, water soluble and has a maximum absorption at 654 nm with a molar absorptivity of 2.103×105 l.mol-1.cm -1. Beerُ s law is obeyed in the concentration range of 0.5 to 14 µg of mesalazine in a final volume of 25 ml. The proposed method has been applied successfully for determination of mesalazine in pharmaceutical preparation (capsule).